Confirmatory factor analysis of an instrument to assess quality in pharmacy service of highly-active antiretroviral therapy program - Chaitha W. (2014)
The purpose of this study was to validate the instrument scale to measure patients' perception of quality in pharmacy service of the highly active antiretroviral therapy (HAART) program. The PSQ-HAART instrument which was developed, with an underpinning in the Gap Theory, in pharmacy context of the HAART program in community hospital in Chiang Rai province, was revised based on confirmatory factor analysis and replication of item analysis. Psychometric test was conducted during February 2005 among a random sample of 200 patients from HIV clinic at four community hospitals in Chiang Rai province. A total of 199 questionnaires were returned (99.5 % response rate). Of these, 183 questionnaires were used for data analysis. The results indicated that the instrument had high internal consistency reliability and construct alidity. A six-factor structure: tangible-reliability, assurance-empathy, empathy, responsiveness I, responsiveness-assurance and responsiveness II was confirmed. The results also indicated that the 33-item scale had better fit than the 36-item scale. The instrument may allow pharmacy administrators to assess quality in pharmacy service when necessary, develop methods to balance service quality with knowledge/skill prior to providing service. Further testing of the instrument would provide more comprehensive evidence for its construct validity when assessing quality in pharmacy context of the HAART program of the country.